Iron fertilization enhanced net community production but not downward particle flux during the Southern Ocean iron fertilization experiment LOHAFEX. Issue 3 (30th August 2013) - Martin, Patrick; van der, Michiel Rutgers; Cassar, Nicolas; Vandromme, Pieter; d'Ovidio, Francesco; Stemmann, Lars; Rengarajan, R.; Soares, Melena; González, Humberto E.; Ebersbach, Friederike; Lampitt, Richard S.; Sanders, Richard; et al.
Abstract [1] A closed eddy core in the Subantarctic Atlantic Ocean was fertilized twice with two tons of iron (as FeSO4), and the 300 km2 fertilized patch was studied for 39 days to test whether fertilization enhances downward particle flux into the deep ocean. Chlorophyll a and primary productivity doubled after fertilization, and photosynthetic quantum yield (FV/FM) increased from 0.33 to ≥0.40. Silicic acid (<2 µmol L−1) limited diatoms, which contributed <10% of phytoplankton biomass. Copepods exerted high grazing pressure. This is the first study of particle flux out of an artificially fertilized bloom with very low diatom biomass. Net community production (NCP) inside the patch, estimated from O2:Ar ratios, averaged 21 mmol POC m−2 d−1, probably ±20%. 234Th profiles implied constant export of ~6.3 mmol POC m−2 d−1 in the patch, similar to unfertilized waters. The difference between NCP and 234Th‐derived export partly accumulated in the mixed layer and was partly remineralized between the mixed layer and 100 m. Neutrally buoyant sediment traps at 200 and 450 m inside and outside the patch caught mostly <1.1 mmol POC m−2 d−1, predominantly of fecal origin; flux did not increase upon fertilization. Our data thus indicate intense flux attenuation between 100 and 200 m, and probably between the mixed layer and 100 m. We attribute the lack of fertilization‐induced export to silicon limitation of diatoms and reprocessing of sinking particles by detritus feeders. Our data are consistent with the view that nitrate‐rich but silicate‐deficient waters are not poised for enhanced particle export upon iron addition.